Effects of Hypertension with and without Smoking on Salivary Electrolytes Concentration - AlRamadany, Maha A.; Yas, Layla S. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Hypertension with smoking is a chronic medical condition that impacts human health. It has been proved that it could be a significant risk factor for different disorders like brain damage, and lung disease and has been related to the growth of oral diseases. However, there are few and conflicting research on its effect on salivary electrolyte concentrations. Objectives: To assess the effect of hypertension with and without smoking on electrolyte concentrations in saliva and to identify its effect on normal oral balance. Methods: A total number of 90 subjects were included, which is comprised of (49) (54.4 %) male subjects and (41) (45.6 %) females subjects in the gender. They were divided into three groups, G1, G2 and G3 groups. Group 1 comprised 30 subjects of hypertension with smoking, Group 2 comprised 30 subjects of hypertension without smoking and Group 3 comprised 30 subjects of healthy non-smoking controls. Results: Findings displayed a highly significant difference in concentration of calcium in saliva and there was no significant difference in potassium and sodium for the three groups. There was a significant difference of calcium in saliva concentration for all study group with respect to P-Value (0.000). Conclusion: The salivary calcium concentration in the saliva can be affected by hypertension with smoking and the increase in salivary calcium levels might be a risk factor for the development of periodontal diseases.